Pengaruh kualitas audit, audit tenure dan auditor switching terhadap opini audit going concern - Sinaga, Agnes Novita Sari; Hamzani, Umiaty; Desyana, Gita (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to examine the effect of audit quality, audit tenure, and auditor switching on going concern audit opinions in Indonesian state-owned enterprises (SOEs), with company size as a moderating variable. Methods – A purposive sampling technique was used to select 145 observations from 30 SOEs between 2019 and 2023. Logistic regression analysis was conducted using SPSS version 25. Findings - The results indicate that audit quality negatively affects the issuance of going concern opinions. Company size significantly moderates the relationship between audit quality and going concern opinions. However, audit tenure and auditor switching do not have a significant impact. Implications - These findings provide insights for management to enhance performance to reduce the risk of receiving going concern opinions, and for auditors to maintain independence and transparent communication during audits. Originality - This research introduces company size as a moderating variable in the relationship between auditor-related factors and going concern audit opinions, specifically in the context of SOE.